Impact of high‐sensitivity cardiac troponin I assays on patients presenting to an emergency department with suspected acute coronary syndrome. Issue 3 (4th August 2014) - Yip, Thomas P Y; Pascoe, Heather M; Lane, Stephen E
Abstract: Objective: To determine whether introduction of high‐sensitivity cardiac troponin I (hscTn‐I) assays affected management of patients presenting with suspected acute coronary syndrome (ACS) to the emergency department (ED) of a tertiary referral hospital. Design, patients and setting: A retrospective analysis of all patients presenting to the Geelong Hospital ED with suspected ACS from 23 April 2010 to 22 April 2013 —2 years before and 1 year after the changeover to hscTn‐I assays on 23 April 2012. Main outcome measures: Hospital admission rates, time spent in the ED, rates of coronary angiography, rates of percutaneous coronary intervention (PCI) and coronary artery bypass graft surgery (CABGS), rates of discharge with a diagnosis of ACS, and rates of inhospital mortality. Results: 12 360 consecutive patients presented with suspected ACS during the study period; 1897 were admitted to Geelong Hospital in the 2 years before and 944 in the 1 year after the changeover to hscTn‐I assays. Comparing the two patient groups, there was no statistically significant difference in all‐hospital admission rates (95% CI for the difference, − 3.1% to 0.3%; P  = 0.10) or proportion of patients subsequently discharged with a diagnosis of ACS (95% CI for the difference, − 2.3% to 5.4%; P  = 0.43). After the changeover, the median time patients spent in the ED was 11.5% shorter (3.85 h v 4.35 h; 95% CI for the difference, − 0.59 to  − 0.43; P  < 0.001) and the proportion of admitted patients undergoing coronary angiography was higher (53.4% v 45.2%; 95% CI for the difference, 4.3 to 12.0 percentage points; P  < 0.001), but there was no statistically significant rise in the proportion of patients who had invasive treatment (PCI and/or CABGS) (95% CI for the difference, − 0.4% to 6.3%; P  = 0.08). Inhospital mortality rates from ACS did not change significantly (95% CI for the difference, − 1.5% to 0.8%; P  = 0.43). Conclusion: The introduction of hscTn‐I assays appeared to be associated with more rapid diagnosis, resulting in less time spent in the ED, without a change in hospital admission rates. A higher proportion of patients had coronary angiographies after the changeover, but there was no significant change in rates of invasive treatment or inhospital mortality.